PROTECTION OF CHILDREN FROM CRIMINAL ACTION IN THE IMPLEMENTATION OF A CHILD-FRIENDLY-CITY - Septiana Prameswari (Perspektif, 2020)
Since Indonesia ratified the Convention on the Rights of the Child in the form of the Child Protection Act, the government has now started to pay attention to child issues. Children are in a period of growth, development, and achievement, in which children very easily absorb everything that happens to them, whether good or bad. Sadly, recently, many children have experienced criminal acts that have caused injuries to the children, not only physical injuries but also psychological/mental injuries. The problem of child protection is not only referring to children who are victims of criminal acts that receive legal protection, but also children of witnesses and children of criminal offenders who have the same legal protection needs. Various Problems of violence against children that occur and even polemics in households that consider violence against children is a natural way of educating children has become piecework for the government to protect children from other violent crimes. Currently, the government is trying to build a suitable city structure for children to live in. The regional government’s role, all law enforces, and the community is to manifest legal protection for children in a Child-Friendly-City structure.